Optimalisasi Produktivitas Overburden Menggunakan Metode Quality Control Circle (QCC) Untuk Evaluasi Ketidaktercapaian Target Produksi Bulan Desember Tahun 2019 Pada PT. Triaryani Kabupaten Musi Rawas Utara, Sumatera Selatan - Fauzan Sumarta; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. One step to control the rate of productivity and accuracy in achieving monthly plans is to observe or optimize the performance of the loading and unloading equipment. This is what PT Triaryani did in evaluating the performance of the production department in excavating overburden material. Data for December 2019 shows that the planned production target of 45,000 tons of overburden was only 41,740 tons. A production management study was carried out by applying the Quality Control Cycle (QCC) method. This method makes it possible to conduct an evaluation on performance of heavy equipment and the obstacles experienced during production process. The study begins by recalculating the initial conditions by considering its mining equipment used, namely Excavator CAT 330 and DT Hino FM 260 JD. The actual productivity of 1 unit of Exca CAT 330 reached 74,113 tons with 80.66% utility equipment and DT Hino FM 260 JD reached 41,607 tons with 4 DT units with 79.32% utility equipment, machine match factor reached 0.48, After evaluating Fishbone Diagram, it was found 4 main problems namely external factors, environment, equipment and man power that affect work time. Performance improvement recommendations based on Paretto Diagrams, are considered to optimize work time. The results show that productivity of 1 unit of exca CAT 330 increased to 15% with utility reaching 86.89% ie 86,000 tons and 4 units of DT increasing 40% with utility equipment reaching 86.52% ie 63,741 tons, machine match factor reached 0.61. These results indicate that performance of heavy equipments could be improved to achieve the monthly overburden material production target. Keywords : Overburden, Productivity, Exca CAT 330, DT Hino, and QCC Methode